Innovative view on the formation of a methodology for managing the quality of corporate assets - V. V. Manuylenko; M. V. Galazova (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The disparate, fragmented nature of corporate asset quality management and assessment methods, reflecting only certain, not all aspects of the state of corporate assets, necessitates the formation of a corporate asset quality managementmethodology based on an innovative view.Goal. The purpose of the study is to form the methodology for managing and evaluating the quality of corporate assets based on a set of general and special principles, combining a set of scientific and practical approaches, methodologies and methods, tools for managing and evaluating assets.Materials and methods. In the course of the research, the works of Russian and foreign authors reflecting the content of the asset management process of commercial organizations, having a fragmentary nature, not reflecting the complex of problems manifested in asset management, are studied.Results and discussion. The study found that the quality of corporate assets integrates the parameters of liquidity, profitability, riskiness, etc. It is argued that from the standpoint of the portfolio approach, the quality of each corporate asset affects the overall quality of the asset portfolio. Differences between the quality of corporate assets and the quality of their management are established. The methodological basis for studying the quality of corporate assets is considered, integrating historical-genetic, classification, complex, systemic, logical, portfolio, functional, strategic, conceptual, cost, scientific approaches, each of which is based on general and special principles.Conclusion. As a result, the authors’ view on the formation of a methodology for managing and evaluating the quality of corporate assets is presented, synthesizing complementary approaches, models, methodologies, methods, methods, techniques, tools for managing the quality of corporate assets, grouped according to various criteria, based on general and special principles.